Documentary film as platform to study the history of heavy metal music and the stereotypical views towards the music and the metalheads - Martinez, Erick Jason G.; Doloricon, Leonilo (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Metalheads have common experience in terms of negative stereotypes from other people, it affects the progress of a metalhead to keep on listening to metal music an drastically change their way of living such as fashion, attitude, and emotions. Metalheads are seen as addicts, creeper and troublemakers. Many of these stereotypical views are deeply rooted in heavy metal music history due to the schizophrenia issue and rebellion back then. There are many cases of these back then but it doesn't mean that we can prejudge a person just because of his/her devotions towards the music. Heavy metal music took control on socio-political, brutally blunt social commentary, social injustice lyrical content back then and many were inspired to write a song and continue the legacy of the pioneers of the music. In the Philippines, the success of local bands such as Greyhoundz, Queso, and Slapshock portrayed the success of heavy metal scene in the country. The objective of this study is to straighten the misconception towards the metalheads through a documentary film who will play the huge role in the development of heavy metal culture. The main audience are the parents who are opposed to heavy metal music because of its negative image and wrong accusation. The main research as a method to this study is ethnography - participant observation field. As a metalhead, the researcher ventured out from his usual group and bandmates and immersed himself in different metalheads on gigs, here in Metro Manila. Many metalheads are very disciplined and responsible people and yet also experience the effects of the negative stereotypical view. Stereotypical views cannot be ceased, but at least can be curtailed by giving the people precise information about 'the music and the fans' will lessen the misconceptions about it. Those affected by stereotypical views will experience difficulties in pursuing their hobbies and dreams; not just in music, but in general terms.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 41-44
Keywords: Documentary films; Heavy metal (Music); Metalhead